Immobilized Laccase biocatalysts as a way to improve degradation of micropollutants from water - Pinheiro, Bruna Bandeira (2021)
Over the last years, design a green and environmentally biocatalyst to improve water quality emerges as one of the most relevant studies nowadays. Among the micropollutants present in water are acetaminophen and mefenamic acid, two drugs widely used to treat pain and fever around the world. They are related to asthma and increased toxicity of the central nervous system. Laccase-based biocatalysts have gained attention to degrade micro-pollutants. Laccase catalyzes the oxidation of phenolic substrates and has many applications which make this enzyme suitable and attractive for industrial applications. However, soluble laccases have diminished availability due to loss of stability, high cost of production, and non-reusability. In this way, laccase immobilization emerges as a way to make these potential applications a reality. In the first approach of this work, chemical amination of laccase following by ionic adsorption on cationic and anionic supports was performed in order to improve the laccase properties. The amination process introduces amino groups on the enzyme surface and may be controlled by the 1-ethyl-3-(3-dimethylamino propyl) carbodiimide (EDAC) concentration. Three quantities of EDAC were tested (0.024 g, 0.048 g e 0.168 g), evidencing that the stability of the laccase improves as more amino groups are introduced. In the second approach of this work, a study of laccase layer-by-layer immobilization onto chitosan activated with genipin or glutaraldehyde was performed. In this way, laccase multilayers were prepared following different combinations of genipin and glutaraldehyde to prepare the first and second laccase layers. This technique was chosen to enhance the loading capacity of the support; however, the addition of a second layer did not always produce a more active biocatalyst. Finally, the biocatalysts produced were used in the degradation of acetaminophen and mefenamic acid. The genipin-coated double-layer biocatalysts promoted greater removal of contaminants with 100% degradation of mefenamic acid and 66% of acetaminophen, under the conditions tested.